Effect of solvent type on the dispersion quality of spray-and freeze-dried CNCs in PLA through rheological analysis. (15th September 2021) - Özdemir, Burcu; Nofar, Mohammadreza
Abstract: Polylactide (PLA) nanocomposites with spray-and freeze-dried cellulose nanocrystals (i.e., SCNC and FCNC) were prepared through solution casting using four different solvents: tetrahydrofuran (THF), chloroform (CHL), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO). Small amplitude oscillatory shear rheological analysis was extensively employed to explore the CNC dispersion quality in PLA. Overall, the rheological properties differences of PLA/SCNC and PLA/FCNC nanocomposites were not very significant. Moreover, the use of THF and CHL did not lead to a proper dispersion of CNCs in PLA due to their low dielectric constants. On the other hand, while the use of DMF was effective on the enhancement of CNC dispersion, DMSO could more dramatically lead to such enhancement due to its higher dielectric constant. The percolation threshold in PLA/SCNC nanocomposites prepared with DMF and DMSO was predicted around 1.52 and 0.12 wt% CNC, respectively. The crystallization behavior of PLA/nanocomposites prepared with DMF and DMSO were also explored. Graphical abstract: Unlabelled Image Highlights: CNC dispersion quality in PLA was explored using THF, CHL, DMF, & DMSO solvents. Dispersion of spray-and freeze-dried CNCs in PLA was also examined. Solvents with higher dielectric constant were crucial for better CNC dispersion. Dispersion of spray-and freeze-dried CNC was to somewhat similar in PLA. Use of DMF & DMSO reduced the CNC percolation threshold down to 1.52 & 0.12 wt%.